Solution of a Differential Equation by Yashu’s Method - et. al., YashwantSingh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, the author has defined a new method“Yashu method” to get an approximate value of a variable by converting the differential equation first in second kind of volterra integral equation or second kind of Fredholem integral equation, after that by solving the above equation we can find approximate value. The author also compared the result by other known results e.g. Laplace transforms method, Picard’s method, Euler’s method and Runge-Kutte method and checked all the result with the exact value.